Pastoralists preferences for cattle traits: Letting them be heard - Ouma, Emily A.; Abdulai, A.; Drucker, Adam G. (2006)
This paper investigates preferences for cattle traits among a pastoral community in a trypanosomosis prevalent area in Kenya. Choice experiments and mixed logit models are employed to estimate economic values of preferred traits which could be introduced through systematic breeding in breed improvement programs that utilise trypanotolerance trait. The findings suggest preference for traits linked to drought tolerance, high live weight, trypanotolerance and fecundity. Identification and estimation of preferred traits provides useful information for breeding policy and provides a framework for promoting conservation of breeds that possess adaptability traits, critical for arid and semi-arid areas.